2006
DOI: 10.1161/circulationaha.105.545863
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Magnetic Resonance Imaging Mapping the Fiber Architecture Remodeling in Human Myocardium After Infarction

Abstract: Background-Diffusion tensor magnetic resonance imaging (DT-MRI) provides a means for nondestructive characterization of myocardial architecture. We used DT-MRI to investigate changes in direction-dependent water diffusivity to reflect alterations in tissue integrity (trace apparent diffusion coefficients [ADCs] and fractional anisotropy [FA]), as well as indicators of remodeling of fiber helix angles, in patients after myocardial infarction. Methods and Results-Thirty-seven patients (35 men, 2 women; median ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
233
7
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(268 citation statements)
references
References 40 publications
(53 reference statements)
27
233
7
1
Order By: Relevance
“…Until now, only two studies have been reported that utilized MR DTI to directly investigate the LV fiber structural changes after infarction (28,30). Chen et al (28) investigated the infarcted region in ex vivo rat hearts with anteroapical infarct 4 weeks after proximal LAD ligation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Until now, only two studies have been reported that utilized MR DTI to directly investigate the LV fiber structural changes after infarction (28,30). Chen et al (28) investigated the infarcted region in ex vivo rat hearts with anteroapical infarct 4 weeks after proximal LAD ligation.…”
Section: Discussionmentioning
confidence: 99%
“…The helix angles were calculated pixel by pixel within the slice and their histogram distribution was analyzed using 10°steps. Three groups of fibers were classified based on fiber orientation: left-handed helical fiber (LHF) with helix angle within Ϫ90°to Ϫ30°in epicardium, circumferential fiber (CF) within Ϫ30°to 30°, and right-handed helical fiber (RHF) within 30°to 90°in endocardium (30). Percentages of three groups of fibers were computed in adjacent and remote regions.…”
Section: Mr Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…changes at cellular level. As in vivo heart DTI is becoming feasible in humans (30), DTI characterization may lead to new clinical means to assess and monitor the myocardial structure and function in developmental or congenital heart diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Among the possible causes, the differences in the cardiac fiber architecture could be an promising topic. The heart is composed of myocardial fibers organized in a complex laminar structure [18,10], and the cardiac fiber structures have an important role in electrophysiology [8], in mechanical functions [4], and in remodeling [23] of the heart. Changes in the fiber structures are for instance inherent in myocardial hypertrophy [9,19,6].…”
Section: Introductionmentioning
confidence: 99%